Peningkatan Pemahaman Siswa Dalam Pembelajaran PAI (Praktek Shalat Jenazah) Melalui Metode Demontrasi Di SMA PGRI Kedamean Gresik - Zuli Agustini; Imam Bahrozi; Muhammad Bisri (Jurnal Pendidikan Agama Islam Miazhar, 2023)
SMA PGRI Kedamean Gresik not only prioritizes general knowledge, but Islamic religious education is also one of the main subjects for every student. So students are required to be able to understand and master material related to Islamic religious education. Islamic Religious Education is a subject that must be taught in the school curriculum from elementary to tertiary education. One of the subjects of Islamic Religious Education is Fiqh. Fiqh is the most difficult material. Even though the material is about prayer, fasting, zakat, funeral arrangements, pilgrimage, and umroh. Where the material is an Islamic teaching that is mandatory for all students. Given the many discussions on fiqh, researchers will focus more on examining the chapter on the management of corpses regarding funeral prayers. For this reason, researchers will discuss increasing students' understanding in learning PAI (practice of funeral prayers) through the demonstration method at SMA PGRI Kedamean Gresik. The problem of this research is how to apply the demonstration method in learning fiqh material for funeral prayers for class XI IPA/IPS at SMA PGRI Kedamean Gresik? and Can the application of the demonstration method increase understanding and improve student learning outcomes of the material for the funeral prayer at SMA PGRI Kedamean Gresik?. Therefore, the purpose of this study was to find out the application of the demonstration method in learning fiqh material for funeral prayers for class XI IPA/IPS at SMA PGRI Kedamean Gresik and to find out how the application of the demonstration method can improve understanding and improve student learning outcomes for class XI IPA/ IPS at SMA PGRI Kedamean Gresik. The benefit of this research is to develop a repertoire of knowledge in the field of education, especially regarding the importance of applying demonstration methods in learning and increasing understanding of learning fiqh material for funeral prayers. The research methodology used was classroom action research which was carried out in stages. The subjects in this study were students of class XI IPA/IPS SMA PGRI Kedamean Gresik. In this study, the data collection methods used were observation, tests, and documentation. The results obtained in this study are that the application of the demonstration method can improve understanding and student learning outcomes. This can be seen from the post-test results of each cycle, namely cycle I (71.21%), cycle II (85%), the scores of students who have reached the KKM have been achieved.